Fatal Carbapenem Resistance Development in Pseudomonas Aeruginosa Under Meropenem Monotherapy, Caused by Mutations in the OprD Outer Membrane Porin. Issue 4 (April 2019) - Fluit, Ad C.; Rentenaar, Rob J.; Ekkelenkamp, Miquel B.; Severs, Tim T.; Mavinkurve-Groothuis, Annelies M. C.; Rogers, Malbert R. C.; Bruin, Marrie C. A.; Wolfs, Tom F. W.
Abstract : A 13-year old neutropenic boy succumbed to bacteremia and sepsis with a Pseudomonas aeruginosa strain that rapidly developed resistance to carbapenems during meropenem monotherapy. Whole genome sequencing of the susceptible and resistant blood culture isolates revealed the meropenem-resistant phenotype to be caused by truncation of the OprD gene, which added to a preexisting inactivated mexR gene. Abstract : Supplemental Digital Content is available in the text.